Inheritance of esters and other volatile compounds responsible for the fruity aroma in strawberry - Rey-Serra, Pol; Mnejja, Mourad; Monfort, Amparo (Frontiers in Plant Science, 2022)
Cultivated strawberry, Fragaria x ananassa, has a complex aroma due to the presence of more than 350 volatile organic compounds (VOCs). However, a mixture of only 19 compounds, called Key Volatile Compounds (KVC), can impart the main strawberry aroma. The octoploid nature of the cultivated strawberry species (2n = 8x = 56) adds complexity to the heritance of the accumulation of the volatiles responsible for aroma. An F1 population cross between two breeding parental lines, FC50 and FD54, was phenotyped for aroma by SPME GCMS during six harvests. A total of 58 compounds were identified: 33 esters, nine terpenes, seven aldehydes, four lactones, two furans, one acid, one alkane and one alcohol, of which 14 were KVCs. A total of 179 QTLs were found and 85 of these were detected in at least three harvests, of which 50 QTLs were considered major (LOD>4.0) and detected in five or six analysed harvests. Several clusters of ester QTLs associated to fruity aroma were discovered, such as QTLs for esters that share hexanoate group that were mapped in LG4A (Hexanoate_4A), those that share acetate and octyl groups in LG6A (Acetate_6A and Octyl_6A) or those with the same methyl group in LG7B (Methyl_7B). Different terpene QTLs associated with floral aroma appear grouped in a cluster in LG3C (Terpene_3C). Some of these clusters of QTLs were validated in a second F2 population, a cross of ‘Camarosa’ and ‘Dover’, that was also phenotyped for three years. Selected SNPs from floral and fruity aroma QTLs were tested in a third population, which will most likely be useful for marker assisted breeding (MAB).